EFISIENSI INPUT PRODUKSI USAHA PENDEDERAN IKAN MAS (Cyprinus carpio) DI DESA PONORAGAN KABUPATEN KUTAI KARTANEGARA - M. Sandhi Subarkah; Heru Susilo; Zul Asman Randika (Jurnal Pembangunan Perikanan dan Agribisnis, 2015)
This research aimed to analyze which production inputs that significantly affecting the breeds output and the both input and output variables value in actual and optimal condition. The method in this research was using Cobb-Douglas approach with multiple liniear regreasion analysis and optimalization analysis by input. The result showed Adjusted R square value by 0.334 that indicated the variables of (X1), (X2) and (X3) capable to express the (Y) variable by 33.4% and the remain 66.6% expressed by other variables. According to t-test indicated that feed variable (X2) significantly affecting the breed production variable (Y) with t-test value of 2.454 and significancy value of 0.021, while the pond wide (X1) and worker (X3) variables not significantly affecting the breed production variable (Y) by t-test value 1.433 and 0.177 with significancy value 0.164 and 0.861. The actual condition value for pond wide (X1) was 4,750 m2, 263 kg for feed (X2) and 2.47 hours of working duration for worker (X3). Meanwhile, the optimal value for pond wide (X1) was 6,032.48 m2, 485.90 kg for feed (X2) and 3.61 hours of working duration for worker (X3). The actual condition value for breed production (Y) was 17,167 breeds, while the optimal condition value 31,003 breeds.